CÁC HỢP CHẤT CLERODANE DITECPEN TỪ CÂY DÂY THẦN THÔNG TINOSPRA CORDIFOLIA - Minh, Châu Văn; Kiệm, Phan Văn; Đạt, Nguyễn Tiến; Hằng, Đan Thuý; Nam, Nguyễn Hoài; Cường, Nguyễn Xuân; Bản, Ninh Khắc; Quỳ, Nguyễn Thị; Hương, Hoàng Thanh (Vietnam Journal of Chemistry, 2012)
Tinospora cordifolia (Willd.) Miers (Menispermaceae) has been widely used in Vietnamese traditional medicine for the treatment of numerous diseases such as malaria, pharyngitis, rheumatism, and diabetes. Phytochemical investigation of the methanol extract of Tinospora cordifolia aerial parts led to the isolation of a new clerodane diterpene, 6β-O-β-D-glucopyranosyl-15,16-epoxy-2α-hydroxy-3,7,13(16),14-clerodantetraene-17,12-olid-18-oic acid methyl ester (1), and two known clerodane diterpene borapetoside F (2) and borapetoside B (3). Their chemical structures were determined by extensive spectroscopic methods including FTICR-MS and 1D and 2D NMR. Keywords: Tinospora cordifolia, Menispermaceae, clerodane diterpene.